2013
DOI: 10.1021/mp400337f
|View full text |Cite
|
Sign up to set email alerts
|

Flash Nanoprecipitation: Particle Structure and Stability

Abstract: Flash nanoprecipitation (FNP) is a process that, through rapid mixing, stabilizes an insoluble low molecular weight compound in a nano-sized, polymer-stabilized delivery vehicle. The polymeric components are typically amphiphilic diblock copolymers (BCPs). In order to fully exploit the potential of FNP, factors affecting particle structure, size, and stability must be understood. Here we show that polymer type, hydrophobicity and crystallinity of the small molecule, and small molecule loading levels all affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
132
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(143 citation statements)
references
References 52 publications
9
132
1
Order By: Relevance
“…2Dd) and the TEM images of PPSTs (PEG-PDHA/PEI-PDHA/PTX/siSna/siTwi) (Fig. 2Dc) demonstrated that the additional hydrated layer on the surface of PPSTs could be formed by the PEG, which was consistent with the TEM picture of PEG layer photographed by other researchers [31,32].…”
Section: Physicochemical Characteristics Of Ppstssupporting
confidence: 88%
“…2Dd) and the TEM images of PPSTs (PEG-PDHA/PEI-PDHA/PTX/siSna/siTwi) (Fig. 2Dc) demonstrated that the additional hydrated layer on the surface of PPSTs could be formed by the PEG, which was consistent with the TEM picture of PEG layer photographed by other researchers [31,32].…”
Section: Physicochemical Characteristics Of Ppstssupporting
confidence: 88%
“…FNP has primarily been limited to the encapsulation of hydrophobic molecules with a preferred logP greater than 6 for stable nanoparticle formation [51, 61]. Ion-pairing of weakly hydrophobic and hydrophilic payloads with counter-ions to form hydrophobic salts for complexation with the block copolymer can allow nanoparticle assembly, but this method is not amenable to the loading of most hydrophilic biologics [6, 62].…”
Section: Resultsmentioning
confidence: 99%
“…Flash NanoPrecipitation (FNP) is a continuous and scalable process for forming NPs that is ideally suited for industrial-scale and low-cost production of targeted encapsulated therapeutics (Johnson and Prud'homme 2003a, b;Pustulka et al 2013;Shen et al 2011;Weissmueller et al 2016;Zhu 2014). In this technique, therapeutic actives are precipitated by rapid micromixing with an antisolvent in the presence of amphiphilic block copolymers.…”
Section: Introductionmentioning
confidence: 99%